FEATURES OF THE QUALITY OF LABOR POTENTIAL FOR SMALL BUSINESS - Namazova, Nodira Dzhumaevna (Mental Enlightenment Scientific-Methodological Journal, 2023)
In the context of ongoing market-structural reforms and global scientific and technological progress, the success of the ongoing transformations depends on the comprehensively developed main entrepreneurial force of society - the individual. At the same time, the accumulation of labor potential and its increase require the development of all spheres of public life, economic, social, and legal. In this article, by the method of sociological research, the importance of certain problems in the management of labor potential by small business owners at all stages of their work with personnel is determined, ways to improve the qualitative characteristics of labor potential in small business are determined.